Effect of Heat Treatment on the Structure and Physicochemical Properties of Buckwheat Bran Protein - CHEN Jing, WANG Libo, REN Yanjuan, YAN Minghuan, ZHANG Jie, ZHANG Bin, LIU Wenchao, WANG Haoran, WU Weijing, LUO Denglin (Shipin Kexue, 2024)
To analyze the effect of heat treatment on the structure and physicochemical properties of buckwheat bran protein (BBP), the molecular mass, secondary structure, intrinsic fluorescence spectrum, free sulfhydryl content, disulfide bond content, microstructure, thermal properties, and rheological properties of BBP were characterized before and after heat treatment. The results showed that part of the subunits of BBP were degraded into small polypeptides or oligopeptides. The α-helical structure was transformed into β-sheet, β-turn and random coil, and the contents of free sulfhydryl groups and disulfide bonds were significantly increased. Compared with soy protein isolate (SPI), the peak temperature, denaturation enthalpy, apparent viscosity, storage modulus (G’) and loss modulus (G”) of BBP were significantly lower. The surface of heat-induced gels of BBP was rougher, and there were obvious cracks on the gel wall, indicating that the thermal stability of BBP was lower than that of SPI. In summary, heat treatment could change the structure of BBP, and have different effects on its physicochemical properties.